Anthropogenesis and theology - Rosiński, Franciszek M. (Anthropological Review, 1986)
A significant progress in biblical studies contributed to the decrease or liquidation of the controversy in the interpretation of the origin and evolution of Homo sapiens. Contacts between anthropologists and theologists show a growing tendency, and next to anthropogenesis they refer also to many new problems.